MENINGKATKAN KETERAMPILAN KEAKSARAAN ANAK USAI 5-6 TAHUN MELALUI MEDIA PUZZLE HURUF DI TK KARTIKA II-1 PALEMBANG - Dian Ayu Natasya; Yuni Dwi Suryani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The development of early literacy in children aged 5–6 years is a crucial stage in which children begin to build the foundation for reading and writing. At this age, children generally achieve several milestones such as recognizing alphabet letters, understanding phonemic relationships (sounds and symbols), reading simple words, and writing their own names. Children who are involved in puzzle games tend to understand letter symbols more easily and are able to remember them in an enjoyable learning context.The type of research used in this study was Classroom Action Research (CAR). The initial observation showed that 5 children (33.33%) were still in the category of Beginning to Develop, 1 child (6.66%) was in the category of Developing as Expected, and 3 children (20%) were in the category of Developing Very Well. After the implementation of the first cycle, there was an improvement in children's literacy skills. Three children (20%) were categorized as Beginning to Develop, five children (33.33%) were categorized as Developing as Expected, and three children (20%) were categorized as Developing Very Well.Based on these results, it can be concluded that although there was an improvement in children's literacy skills in the first cycle, the results had not yet reached the predetermined success indicators. Therefore, the researcher continued to the second cycle to improve the shortcomings found in the previous stage in order to obtain more optimal results. The results of the second cycle showed a significant improvement in children's literacy skills through the use of letter puzzle media. At this stage, eight children (53.33%) were in the category of Developing as Expected and seven children (46.66%) were in the category of Developing Very Well. Therefore, the letter puzzle media was considered appropriate and effective to be used as an innovative learning strategy in developing early literacy skills of young children at TK Kartika II-1 Palembang.